Development of H5P Moodle-Based Interactive STEM-Loaded Videos to Grow Performance Skills as an Effort to Overcome Learning Loss in Electrical Measuring Materials - Ida Susanti; Agus Suyatna; Kartini Herlina (Postgraduate, University of Mataram, 2023)
This study aims to develop an interactive STEM-based video based on H5P Moodle that is valid, practical, and effective for cultivating performance skills as an effort to overcome learning loss in the material for measuring instruments. The research method used in this development is the R & D method using the ADDIE model which consists of five development steps namely: analyze, design, development, implementation, and evaluation. The data collection instruments used include: needs analysis questionnaires, validation test questionnaires, practicality test questionnaires, and effectiveness test questionnaires. The trial design using research products shows that the H5P Moodle-based Interactive Video developed is valid, practical, effectively used in the closed-eye learning process (PTTM) through blended learning to foster performance skills as an effort to overcome learning loss. The results of the validity test obtained an average percentage of construction validity of 92.00% and content validation obtained an average percentage of 87.00%. The results of the practicality questionnaire analysis showed that the STEM-based Interactive Video based on the H5P Moodle was stated to be practical with product legibility obtaining a percentage of 96.00% in the very good category. The results of the teacher's response test using Interactive Video with STEM-based H5P Moodle obtained a percentage of 87.60% in the very good category. For student responses the percentage is 87.00%, this indicates an interactive video with STEM content based on the H5P Moodle that was developed practically. Effectiveness is shown by the results of the analysis of the average percentage of achievement of performance skills in the experimental class of 87.50 and 73.00% in the control class. An increase in performance skills of 14.50% shows that Interactive Video with STEM content based on Moodle's H5P is very effective for growing performance skills as an effort to overcome learning loss.